2019
DOI: 10.5114/ada.2019.87447
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of plasma levels of tissue factor and tissue factor pathway inhibitor in patients with psoriasis

Abstract: IntroductionPsoriasis is a chronic, recurrent, inflammatory skin disorder with systemic involvement. It has recently been established that psoriasis is associated with an increased cardiovascular risk. Chronic skin-specific inflammation may promote atherosclerosis. Myocardial infarction or stroke can also be a result of underlying haemostasis disorders. Disorders in fibrinolysis and thrombosis in patients with psoriasis have been observed by many authors.AimThis study points to the key role played by the tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…It has been previously observed that plasma TF and TM levels may be the risk factor for thrombosis [50]. TF synthesis and release is stimulated by cell damage which can induce the proliferation and migration of endothelial cells, and it is involved in inflammation [51]. Consistent with previous reports [52], we also have observed elevated plasma levels of TF and TM…”
Section: Plos Onesupporting
confidence: 92%
“…It has been previously observed that plasma TF and TM levels may be the risk factor for thrombosis [50]. TF synthesis and release is stimulated by cell damage which can induce the proliferation and migration of endothelial cells, and it is involved in inflammation [51]. Consistent with previous reports [52], we also have observed elevated plasma levels of TF and TM…”
Section: Plos Onesupporting
confidence: 92%
“…It has been previously observed that plasma TF levels may be the risk factor for thrombosis [50]. TF synthesis and release is stimulated by cell damage which can induce the proliferation and migration of endothelial cells, and it is involved in inflammation [51]. Consistent with previous reports [52], we also have observed elevated plasma levels of TF in our SARS-CoV2 study cohort compared to controls which was mildly correlated with plasma levels of exosome-associated NE.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that psoriasis is linked to increased cardiovascular risks. Since chronic skin-specific inflammation may promote atherosclerosis, myocardial infarction or stroke may also be correlated with haemostatic disorders; there were dysfunctions of fibrinolysis and thrombosis in patients with psoriasis [29]. Rho GTPases are a major branch of the Ras superfamily and play an important role in the signal transduction pathway of cells [30].…”
Section: Discussionmentioning
confidence: 99%